Need Assessment the Online Counseling Services at School: A Pre-Eliminary Study - Rohmatus Naini; Mungin Eddy Wibowo; Edy Purwanto; Mulawarman Mulawarman; Abdan Syakuro Sugandi (Universitas Negeri Semarang, 2024)
The development of technology in the field of counselling is an opportunity and challenge for counsellors in schools in providing counselling services. The purpose of this study was to analyse the results of students' need assessment in the process of evaluation and follow-up services. This survey involved 167 high school students by distributing questionnaires online. The survey results showed that almost 61.1% of students had experience of receiving guidance and counselling services from school counsellors. The types of services are online, offline and also blended, with the majority being offline sessions. Only 11.4% of students have online counselling experience, the rest do it offline. Some of the obstacles in the counselling process are fear of data being spread, embarrassment, time constraints and conditions, mistruts, inexperience, and not being able to open up, and networks. The evaluation done by students is that the implementation of guidance and counselling services needs to be improved, there is a need for other interaction applications and sometimes it is not optimal. Students like online counselling in the form of texts, websites, phone calls, and video calls. Often the school counsellor has a varied response speed, namely slow, medium and slow. Almost 79.1% felt comfortable during online group counselling with features such as video, articles, online text, graphics, phone, audio, video conference, virtual reality and supporting articles. Almost 63.5% were aware of virtual reality and had high interest. Implications for guidance and counselling and future research recommendations will be discussed in the core of the paper. Perkembangan teknologi di bidang konseling menjadi peluang sekaligus tantangan bagi konselor di sekolah dalam memberikan layanan konseling. Tujuan penelitian ini adalah menganalisis hasil penilaian kebutuhan mahasiswa pada proses evaluasi dan tindak lanjut layanan. Survei ini melibatkan 167 siswa SMA dengan menyebarkan kuesioner secara online. Hasil survei menunjukkan hampir 61,1% siswa mempunyai pengalaman menerima layanan bimbingan dan konseling dari konselor sekolah. Jenis layanannya ada yang online, offline, dan juga blended yang mayoritas merupakan sesi offline. Hanya 11,4% siswa yang memiliki pengalaman konseling online, sisanya melakukannya secara offline. Beberapa kendala dalam proses konseling adalah ketakutan akan data yang tersebar, rasa malu, keterbatasan waktu dan kondisi, ketidakpercayaan, kurangnya pengalaman, dan tidak bisa terbuka, serta jaringan. Evaluasi yang dilakukan siswa adalah pelaksanaan layanan bimbingan dan konseling perlu ditingkatkan, perlu adanya aplikasi interaksi lain dan terkadang kurang maksimal. Siswa menyukai konseling online dalam bentuk teks, website, panggilan telepon, dan video call. Seringkali konselor sekolah mempunyai kecepatan respon yang bervariasi yaitu lambat, sedang dan lambat. Hampir 79,1% merasa nyaman selama konseling kelompok online dengan fitur-fitur seperti video, artikel, teks online, grafik, telepon, audio, konferensi video, virtual reality dan artikel pendukung. Hampir 63,5% mengetahui realitas virtual dan memiliki minat yang tinggi. Implikasinya terhadap bimbingan dan konseling serta rekomendasi penelitian di masa depan akan dibahas pada inti makalah.